2017
DOI: 10.1021/jacs.7b11245
|View full text |Cite
|
Sign up to set email alerts
|

α-C—H Alkylation of Methyl Sulfides with Alkenes by a Scandium Catalyst

Abstract: The C-H addition of sulfides to alkenes is an atom-efficient route for the functionalization and modification of sulfide compounds through C-C bond formation, but this transformation is highly challenging. We report here the regioselective α-C(sp)-H addition of a wide range of methyl sulfides to a variety of olefins and dienes by a half-sandwich scandium catalyst. This protocol provides a unique route for the synthesis of diverse sulfide derivatives through C-C bond formation at a sulfur-adjacent carbon atom i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(37 citation statements)
references
References 41 publications
3
34
0
Order By: Relevance
“…Another biologically active structural motif that can be activated by this catalyst are thioethers, as was well described by Hou and co-workers in 2018 [39]. In this work, the presence of and several alkenes resulted in the successful scandium-C(sp 3 )-H alkylation of methyl thioethers (Scheme 4B), by which different activated internal thioethers were obtained in good yields (Scheme 4C).…”
Section: Review Scandium-catalyzed C-h Activationsupporting
confidence: 60%
See 1 more Smart Citation
“…Another biologically active structural motif that can be activated by this catalyst are thioethers, as was well described by Hou and co-workers in 2018 [39]. In this work, the presence of and several alkenes resulted in the successful scandium-C(sp 3 )-H alkylation of methyl thioethers (Scheme 4B), by which different activated internal thioethers were obtained in good yields (Scheme 4C).…”
Section: Review Scandium-catalyzed C-h Activationsupporting
confidence: 60%
“…Therefore, as challenging as it seems to be, there is still a demand for applying this relevant methodology to obtain new compounds with known pharmacological properties. However, several molecules based on structural scaffolds related to important biological activities have been successfully achieved via scandium-catalyzed C-H activation [37][38][39][40][41]. Hou's group presented various studies on this theme [42,43], such as a notable work recently published in which they promoted a scandium-catalyzed intramolecular cyclization on benzimidazole substrates, via a C-H activation at the C-2 position (Scheme 2B).…”
Section: Review Scandium-catalyzed C-h Activationmentioning
confidence: 99%
“…11 c – e Starting from D, the ligand exchange between 2a and 1a could take place to form a π-complex E. Subsequently, the alkene ligand in E may insert into the Sc–C bond via TS2 (Δ G = 24.6 kcal mol −1 ) to give the five-membered ring intermediate F, as proposed in literature. 3 The re-coordination of a sulfide 1a to the Sc atom easily takes place to give the more stable species G. The protonation of the Sc–alkyl bond via C–H activation of the coordinated-1a in G would finally release the alkylation product 3a.…”
Section: Resultsmentioning
confidence: 99%
“…This is not in agreement with the experimental observation of a significant kinetic isotope effect (KIE ≈ 5), which suggested that the C–H activation of the methyl group in the sulfide should be involved in the rate-determining step. 3 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation